PERAN MORAL DISENGAGEMENT DALAM MEMEDIASI HUBUNGAN PERCEIVED ANONYMITY DAN CYBER AGGRESSION PADA REMAJA PENGGUNA MEDIA SOSIAL - Sonia, Gina; Zakinov Irta, Aflah (Lafadz Jaya Publisher, 2026)
Cyber aggression among adolescents has become increasingly prevalent with the widespread use of social media. One factor contributing to this behavior is perceived anonymity, which may encourage aggressive actions through the mechanism of moral disengagement. This study examined the mediating role of moral disengagement in the relationship between perceived anonymity and cyber aggression among adolescent social media users. A quantitative approach was employed involving 360 adolescents aged 16–21 years. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that perceived anonymity had a positive and significant effect on both moral disengagement and cyber aggression. Moral disengagement also positively influenced cyber aggression and significantly mediated the relationship between perceived anonymity and cyber aggression. These findings suggest that anonymity in social media strengthens aggressive behavior by reducing moral self-regulation. Strengthening digital literacy and adolescents' moral self-regulation is therefore essential to prevent cyber aggression.